Issues of conservation and restoration of two photographic works by Zbigniew Dłubak: Onona and Desymbolisations - Monika Supruniuk (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art, 2013)
This paper is based on MA project, elaborated at Academy of Fine Arts in Warsaw, Poland in April 2011. The article describes conservation and restoration of two art works by Zbigniew Dłubak. Onona is a spatial object composed of large format photography and a man's profile cut out of chipboard. Desymbolisations is a series of 5 photographs. Implementation of an assumption adopted by the author was different for each of the works. The spatial object was conserved and restored, while the series of photographs were digitally reconstructed based on similar prints.